The Oriental Tiny Frog of the Genus Microhyla Tschudi, 1839 (Amphibia: Anura: Microhylidae) Revealed across Geographical Barriers of the Wallace Line - Rury Eprilurahman; Vestidhia Yunisya Atmaja; Misbahul Munir; Amir Hamidy; Tuty Arisuryanti; Rosichon Ubaidillah (Universitas Gadjah Mada, 2021)
The frog genus Microhyla was considered as the South, East, and Southeast Asian frog species. Microhyla orientalis was described in 2013, distributed in Java and Bali, Indonesia. Thenceforth, it was known as the easternmost distribution of this genus within the oriental region, but recently this species was recorded from the Timor Island and Sulawesi on the Wallace regions. We applied molecular analysis to evaluate the taxonomic status and the origin of the Wallacean population. Phylogenetic analysis using the partial 16S mitochondrial gene demonstrated that the Java, Timor and Sulawesi populations were not significantly different from the Bali population. This Wallacean population of M. orientalis was originated from Java and possibly it is accidentally distributed by humans through the expansion of agricultural activity.